Survey of treponemal infections in free-ranging and captive Macaques, 1999–2012 - Amy R. Klegarth (2018)
© 2017, Centers for Disease Control and Prevention (CDC). All rights reserved. Survey results showed treponemal infection among pet macaques in Southeast Asia, a region with a high prevalence of human yaws. This finding, along with studies showing treponemal infection in nonhuman primates in Africa, should encourage a One Health approach to yaws eradication and surveillance activities, possibly including monitoring of nonhuman primates in yaws-endemic regions.